Bond efficacy of recycled orthodontic brackets: A comparative in vitro evaluation of two methods - Vikram Shetty; Yash Shekatkar; Neesu Kumbhat; G Gautam; Shalan Karbelkar; Meghna Vandekar (Wolters Kluwer Medknow Publications, 2015)
Context: Recycling of orthodontic brackets in developing orthodontic economies is an extremely common procedure. Bonding protocols and reliability of these brackets is, however, questionable, and still the subject of research. Aims: The aim was to evaluate and compare the shear bond strength of brackets recycled with sandblasting and silicoating. Materials and Methods: Ninety extracted human premolars were bonded with 0.022" SS brackets (American Orthodontics, Sheboygan USA) and then debonded. The debonded brackets were divided into three groups of 30 each. Group I: Sandblasting with 50-μm aluminum oxide (control group) Group II: Sandblasting with 50-μm aluminum oxide followed by metal primer application Group III: Silicoating with 30-μm Cojet sand followed by silane application and rebonded with Transbond XT. The sandblasted brackets and silicoated brackets were viewed under the scanning electron microscope, immediately after surface conditioning before rebonding. The shear bond strength with each group was tested. Statistical Analysis Used: One-way analysis of variance, post-hoc Scheffe multiple comparison tests. Results: The results showed that sandblasting created more irregularities and deeper erosions while silica coating created superficial irregularities and shallow erosions.